Editorial 2019: (4) 1 - Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2019)
Dear Colleagues, Readers and Contributors of RESSAT! We are excited to be with you through the May 2019 issue (4/1) of Research in Social Sciences and Technology (RESSAT). We would like to extend our appreciations to all who contributes by submitting or reviewing manuscripts or have been readers of RESSAT. In our first issue of the fourth year, you will find six articles. I would like to thank everyone and express my special appreciation to the people who contributed to make this issue ready for you. I especially would like to thank all authors and reviewers for their contribution to RESSAT. I hope you will both enjoy and be challenged by the articles in this issue of RESSAT. I also look forward to seeing your contribution to the development of RESSAT in the future.